Comparison of Cellulose Extraction Methods from Lontar (Borassus flabellifer) and Salak (Salacca zalaacca) Fronds - Rusdin, Aisyah; Harun, Rahmah; Yunita, Vivi Alfi; Awaluddin, Awaluddin (Jurnal Beta Kimia, 2025)
Palmyra fronds and salak fronds are waste products from the palmyra and salak plants that have not been optimally utilized. However, the high cellulose content in these fronds offers potential applications across various fields. This study aimed to extract and compare cellulose from lontar (Borassus flabellifer) and salak (Salacca zalacca) frond waste using two methods: alkaline sodium hydroxide (NaOH) solvent and nitric acid (HNO₃) hydrolysis. After soaking and heating, the extraction was performed through a bleaching process. The yield results showed that lontar fronds produced the highest yield of 64.22% using the acid hydrolysis method, while salak fronds yielded 46.8%. The cellulose obtained from lontar fronds was gray, and from salak fronds, it was white, indicating differences in purity. After treatment, the disappearance of the carbonyl group (C=O) in the FTIR functional group analysis indicated successful delignification. Common cellulose functional groups such as O-H, C-H, and C-O, as well as β-1,4 glycosidic bands, were detected at wave numbers 895-897 cm⁻¹, indicating that the cellulose structure was well preserved. Cellulose from both lontar and salak fronds has great potential to serve as an environmentally friendly alternative raw material for applications in bioplastics, bioethanol, and other cellulose derivatives.